L’objet de l’art : Cassirer et Fiedler - Rémi Mermet (Recherches Germaniques)
This paper aims to understand why Ernst Cassirer never published his short but far-reaching reflections on Konrad Fiedler’s theory of art. While both thinkers do share a vision of art as a way to shape (and not simply to imitate) reality, I suggest that they have very different conceptions of artistic objectivity: Cassirer emphasises the symbolic (and therefore cultural) nature of the work of art; Fiedler focuses on the creative process itself, conceived of as an endless elucidation of visibility. In so doing, I demonstrate that Fiedler’s doctrine is not fully compatible with the philosophy of symbolic forms – hence perhaps Cassirer’s reluctance to address the issue publicly.